Referenciales en la intención y decisión de compra de Smartphone en los estudiantes universitarios de Guayaquil - Sumba Nacipucha, Nicolas Armando (2018)
The whirlwind of models and brandsin the smartphone market forces the consumer to face the decision of purchase process before a range of devices with a variety of benefits and prices, this research examines the intention and decision to purchase smartphones, as well as the exogenous and endogenous factors that influence university students in Guayaquil when they face these processes. The questionnaire was applied to a sample in six different university centers, and scientific observation was also used as an objective and systemic process. One of the results identifies the need of university students to have a smartphone as a technological tool that, apart from providing a series of benefits, confers a perception of acceptance and social status, the work exposes the results so that they canbe used as a reference for future marketing strategies by brands.